IN VITRO GROWTH CHARACTERISTICS OF MAIZE AND WHEAT ON MICROBIAL INOCULATION - B. SHANKAR NAIK (International Journal of Pharma and Bio Sciences, 2016)
Maize and wheat seeds were inoculated with microorganisms like Chaetomium globosum, Gliocladium roseum, Streptomyces sp. Pseudomonas pseudomallei YL-1 along with control and fertilizer (NPK 17:17:17) were grown in pots for forty five days under laboratory conditions. The phenotypic traits such as shoot length, root length, leaf area were increased significantly in seedlings treated with microbes when compared to control but near equal to fertilizer-treated seedlings. Although the fresh and dry weights were more in microbial treated seedlings over control but did not show significant increase by DMRT analysis. However, based on the results obtained in this study it has been revealed that microbial inoculants could be promising substitutes for chemical fertilizers for the improvement of agricultural crops.